Comparing Conventional and Flipped Classroom Delivery Mode for Teaching Writing at Grade 11 of SMAN 4 Kendari - Baharudin Baharudin; Hilaluddin Hanafi; Sartiah Yusran (Journal of Language Education and Educational Technology (JLEET), 2020)
Flipped classroom is considered to be capable of addressing two classical constraints pertaining to the teaching of writing in an EFL context – limited time for classroom interaction and limited exposure to the target language. However, our current understanding of its true effectiveness with respect to students’ learning outcomes and learning motivation relative to conventional teaching is still in its infancy. In fact, reviewing the literature, it becomes immediately clear that many of the claims in favor of flipped classroom are based primarily on anecdotal, rather than empirical evidence. The present study sought to compare students’ learning outcomes and their motivation as a result of attending two different modes of instruction: conventional task-based face-to-face classroom and task-based flipped classroom. Conducted with students at SMAN 4 Kendari, the study employed a matching pre-post comparison group, involving two cohorts: experimental group (44 students) and control group (42 students). These students were recruited using a purposive sampling technique. The statistical analysis of independent samples t-test suggests that students attending flipped classroom significantly outperform those studying conventionally, p 0.00 < 005. Additionally, it was also found that students attending flipped classroom are significantly more motivated than their counterparts studying conventionally. All in all, a flipped strategy has resulted in both improved learning and motivation of the students. Implications of these findings will be critically discussed in this paper.Keywords: Flipped classroom; Conventional learning; Mode of delivery; Writing; Motivation